Measurement of the W boson helicity in events with a single reconstructed top quark in p p collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2015)
A measurement of the W boson helicity is presented, where the W boson originates from the decay of a top quark produced in pp collisions. The event selection, optimized for reconstructing a single top quark in the final state, requires exactly one isolated lepton (muon or electron) and exactly two jets, one of which is likely to originate from the hadronization of a bottom quark. The analysis is performed using data recorded at a center-of-mass energy of 8 TeV with the CMS detector at the CERN LHC in 2012. The data sample corresponds to an integrated luminosity of 19.7 fb(-1). The measured helicity fractions are F-L = 0.298 +/- 0.028 (stat) +/- 0.032(syst), F-0 = 0.720 +/- 0.039 (stat) +/- 0.037(syst), and F-R = -0.018 +/- 0.019 (stat) +/- 0.011(syst). These results are used to set limits on the real part of the tWb anomalous couplings, g(L) and g(R).
Keywords: Electroweak interaction; Hadron-Hadron Scattering; COUPLINGS